A real-world study of the optimal cut-off value for vancomycin trough concentration associated with outcomes in children infected with drug-resistant Gram-positive bacteria - Yan, Yinghui; Wang, Manli; Zhou, Mi; Yang, Jingxing; Zhu, Zengyan; Wang, Fengjiao (Frontiers in Pediatrics, 2025)
BackgroundDue to a lack of studies on the relationship between vancomycin trough concentration and clinical outcomes in pediatric patients, there is insufficient evidence to provide a unified standard for vancomycin trough concentration for children.MethodsWe retrospectively analyzed the data of drug-resistant Gram-positive bacteria isolated from human germfree samples of 66 children diagnosed as definite infectious diseases. Vancomycin was intravenously delivered and the trough concentration was monitored regularly. Receiver operator characteristic curve (ROC curve) was used to explore the relationship between vancomycin trough concentration and treatment outcome.Results40.9% of the enrolled pediatric patients had poor outcomes. A vancomycin trough concentration above 6.8 mg/L (OR = 0.014, 95% confidence interval 0.001–0.351, P = 0.009) was identified as an independent protective factor, while trough concentrations above 10 mg/L appeared to be necessary to support favorable outcomes within 4 days of treatment in children with secondary bloodstream infections and non-bloodstream infections. 4 (6.35%) patients displayed vancomycin-related acute kidney injury (AKI) with an average trough concentration of 10.85 mg/L, and 50% of them simultaneously used nephrotoxic drugs. Moreover, within 7 days of vancomycin administration, there was a significant decrease in serum creatinine and an increase in creatinine clearance rate, and the children with augmented renal clearance exhibited significantly lower vancomycin trough concentrations and higher proportion of poor outcomes.ConclusionA vancomycin trough concentration above 6.8 mg/L is sufficient to support favorable outcomes in children who were infected with drug-resistant Gram-positive bacteria. Compared with vancomycin-associated AKI, augmented renal clearance and subsequent poor antibiotic treatment outcome deserve more attention.